A comparative study of the effect of submicron porous and smooth ultrafine‐grained Ti‐20Mo surfaces on osteoblast responses. Issue 7 (17th April 2018) - Gui, Na; Xu, Wei; Abraham, Amanda N.; Myers, Damian E.; Mayes, Edwin L. H.; Xia, Kenong; Shukla, Ravi; Qian, Ma
Abstract: The surface of an orthopaedic implant plays a crucial role in determining the adsorption of proteins and cell functions. A detailed comparative study has been made of the in vitro osteoblast responses to coarse‐grained (grain size: 500 μm), ultrafine‐grained (grain size: 100 nm), coarse‐porous (pore size: 350 nm), and fine‐porous (pore size: 155 nm) surfaces of Ti‐20Mo alloy. The purpose was to provide essential experimental data for future design of orthopaedic titanium implants for rapid osseointegration. Systematic original experimental data was produced for each type of surfaces in terms of surface wettability, cell morphology, adhesion, growth, and differentiation. Microscopic evidence was collected to reveal the detailed interplay between each characteristic surface with proteins or cells. Various new observations were discussed and compared with literature data. It was concluded that the coarse‐porous surfaces offered the optimum topographical environment for osteoblasts and that the combination of ultrafine grains and considerable grain boundary areas is not an effective way to enhance cell growth and osteogenic capacity. Moreover, pore features (size and depth) have a greater effect than smooth surfaces on cell growth and osteogenic capacity. It proves that cells can discern the difference in pore size in the range of 100–350 nm. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 2020–2033, 2018.